Contribuição à análise de proveniência sedimentar pelo método Traços de Fissão em zircão e influências estruturais para a formação do Planalto Residual de Marília - Santos, Caio Augusto Marques dos [UNESP]; Nunes, João Osvaldo Rodrigues [UNESP]; Sáenz, Carlos Alberto Tello [UNESP] (Revista Brasileira de Geomorfologia, 2014)
Marília Residual Plateau is constituted as a typical board shaped relief of sedimentary basin center. Its formation generated a big summit compartment interconnected to secondary summits of minor extension. The domain of the hillsides fi nishes at abrupt slopes with 50 to 100 meters invernesses which delimitate and surround the plateau. Due to its singular relief forms it was aimed to understand its genesis and evolution, since its sedimentary source up to the constitution as residual plateau. In order to reach this aim it was used dating through fi ssion track method in 68 Zircon grains collected from rocks of Marília Formation in the city of Marília – SP, and through the use of bibliographical review understand the structural infl uences on the genesis of Marília Residual Plateau. The ages, which varied from 640 to 80 million years, suggest different thermotectonic events in different areas of rock-source supplier of detritic material. Concerning to the structural infl uences, they are connected to the weak zones of Paraná Basin basement. The diverse geological formations superimposed inherited these characteristics of the crystalline basement through structural alignments. The post cretaceous epeirogenesis accelerated the rivers which fl owed to west towards Paraná River and this provided the beginning of the plateau isolation in the landscapes of west of São Paulo state. In the gondwanic separation context, the tensions which came from tectonic efforts generated breakable deformation in the rocks of Marília Formation, levels of local basis where started the hydrographic system organization and the plateau sculpture.

O Planalto Residual de Marília constitui-se como um típico relevo tabuliforme de centro de bacia sedimentar. Sua formação gerou um grande compartimento de topo interligado a topos secundários de menor extensão. O domínio das vertentes encerra-se em escarpas abruptas com desníveis de 50 a 100 m, que delimitam e circundam o planalto. Devido as suas formas peculiares de relevo, buscou-se compreender sua gênese e evolução, desde suas fontes de sedimentos até constituição como planalto residual. Para tanto, utilizou-se a datação via método traços de fi ssão em 68 grãos de zircão coletados de rocha da Formação Marília na cidade de Marília-SP. E, através de revisão bibliográfi ca, procurou-se também entender as infl uências estruturais para a gênese do Planalto Residual de Marília. As idades, que variaram de 640 até 80 Ma, sugerem diferentes eventos termotectônicos em diferentes áreas de rochas-fontes fornecedoras de material detrítico. Acerca das infl uências estruturais, elas estão ligadas a zonas de fraqueza do embasamento da Bacia do Paraná. As diversas formações geológicas superpostas herdaram essas características do embasamento cristalino por meio dos alinhamentos estruturais. A epirogênese pós-cretácica acelerou os rios que rumavam para oeste em direção ao Rio Paraná, o que proporcionou o início do isolamento do planalto na paisagem do oeste paulista. No contexto de separação gondwânica, as tensões provindas dos esforços tectônicos geraram deformações rúpteis nas rochas da Formação Marília, níveis de base locais por onde se iniciou a organização do sistema hidrográfi co e a esculturação do planalto.
Contribution to the analysis of sedimentary provenance by Fission Track method in zircon and structural influences to Marília’s residual plateau formation
Keywords: Marília residual plateau; Fissiontrack; Structures; Planalto residual de Marília; Traço de fissão; Estruturas